Draft Annual Plan 1976-77 Govt. of Arunanchal Pradesh October-1975 - Planning Commission (Planning Commission, 1975)
The Fifth Five Year Plan outlay tentatively fixed by the Planning Commission for Arunachal Pradesh was Rs. 6330.00 lakhs. During the first .year 1974-75 an actual expenditure of Rs. 664.37 lakes has been reported against I plan allocation of Rs.725.00 lakhs. During 1975-76, there has been an allocation of Rs. 765.00 lakhs. Expenditure luring the first two years of the Plan can therefore not exceed a total of Rs. 1429.37 lakhs or a total of 22.6 per cent of the original plan allocation. This leaves 5 according to the original Fifth Plan Outlay, a total of Rs. 4900.63 lakhs for schemes to be implemented during the three years beginning from 1976-77.
Government of Arunachal Pradesh
Keywords: Area Development; Panchayati Raj; Labour Welfare; Craftsmen Training; Roads and Bridges; Power Development; Civil Aviation; Rural Housing; Social & Cultural Affairs; Minimum Needs; Programme; Royalty In Forest-Produce; Motor vehicles Taxes; Miscellaneous Receipts; Economy